2000
DOI: 10.1001/archpedi.154.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Clinical Judgment in Neonatal Jaundice

Abstract: Clinical examination with visual assessment for jaundice in newborns is neither reliable nor accurate. The decision to perform serum bilirubin testing should be based on additional factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 9 publications
8
113
0
1
Order By: Relevance
“…Most previous studies on the clinical assessment of neonatal hyperbilirubinemia were conducted in the United States or Europe, were limited to a single or bi-ethnic study population and evaluated the clinical assessment of jaundice by a single observer compared to a serum bilirubin measurement taken in all the enrolled subjects (Supplementary Table 1). [5][6][7][8][9][10][11][12] Riskin et al 6 showed that neonatologists' identification of jaundice, and predicted serum bilirubin levels based on the Kramer scale, was highly correlated with serum total bilirubin levels (r ¼ 0.682, P<0.001). This study concluded: 'the clinical impression of jaundice by anyexperienced clinician is a reliable method to assess newborns for y(neonatal hyperbilirubinemia) and serum bilirubin levels are necessary only in severely jaundiced neonates.'…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies on the clinical assessment of neonatal hyperbilirubinemia were conducted in the United States or Europe, were limited to a single or bi-ethnic study population and evaluated the clinical assessment of jaundice by a single observer compared to a serum bilirubin measurement taken in all the enrolled subjects (Supplementary Table 1). [5][6][7][8][9][10][11][12] Riskin et al 6 showed that neonatologists' identification of jaundice, and predicted serum bilirubin levels based on the Kramer scale, was highly correlated with serum total bilirubin levels (r ¼ 0.682, P<0.001). This study concluded: 'the clinical impression of jaundice by anyexperienced clinician is a reliable method to assess newborns for y(neonatal hyperbilirubinemia) and serum bilirubin levels are necessary only in severely jaundiced neonates.'…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] We evaluated the validity of an adapted Kramer scale when used by HCW and PHY to evaluate infants <60 days of age, with a focus on neonates aged 1 to 20 days, presenting to community clinics in Karachi, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on various methods of bilirubin estimation in different laboratories, the frequency of breast feeding,ethnic makeup of people and regional variations the incidence of hyperbilirubinemia changes [7][8][9] . The severe jaundice and kernicterus has been found in some healthy full term newborns dischared early with no apparent hemolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lower thresholds for starting phototherapy (PHT) may be appropriate. 3,4 Although TSB measurement is reliable, it is a painful and time-consuming procedure. 1 Bilirubin levels before and during PHT are measured as TSB and obtained by heel stick or venous blood draws.…”
Section: Introductionmentioning
confidence: 99%